The Poincare method for a strongly nonlinear Duffing oscillator - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 2003)
It is well-known that the classical Poincare method is limited to weakly nonlinear systems and for extending the range of validity of this method to strongly non-linear systems, various modifications have been developed